RISK FACTORS FOR TYPES OF DEMENTIA CLASSIFIED ON MULTIVARIATE TRAJECTORIES OF COGNITIVE FUNCTIONS BEFORE INCIDENCE. (11th November 2018) - Amano, H; Kitamura, A; Yokoyama, Y; Narita, M; Nishi, M; Yoshida, H; Fujiwara, Y; Shinkai, S
Abstract: Approximately 10% of the Japanese elderly are dependent and have cognitive impairments according to the Long-Term Care Insurance system. This apparent dementia is assumed to be heterogeneous. We attempted to classify it based on the development of cognitive manifestations preceding dementia, and to identify risk factors specific to the respective types. From 2007 to 2016 in Kusatsu town, 365 subjects developed apparent dementia: a combination of dementia diagnosis or dementia-like signs reported by physicians and dependency certified by the insurance system. In total, 134 of the 365 subjects had been evaluated using the Mini-Mental State Examination (MMSE) during annual health check-ups for the preceding 5 years. The multivariate trajectory model was applied to the repeated measurements of MMSE sub-scores, yielding two major and three minor types of apparent dementia with proportions of 41% and 38%, and 7%, 7%, and 7%, respectively. Risk factors of the two major types were explored using Cox regression analysis that utilized a cohort of the 1053 participants in check-ups who were cognitively intact at the first visit from 2002 through 2010 and followed up until 2016. One of the major types was characterized by early decline in attention and memory; its risk factors were both high and low levels of serum cholesterol, moderately increased glycated hemoglobin and decreased diastolic blood pressure. The other major type was characterized by no cognitive decline as observed in preceding check-ups; its risk factors were smoking, decreased hemoglobin, and decreased albumin. The latter type warrants further research.